2023
DOI: 10.1108/sampj-01-2022-0051
|View full text |Cite
|
Sign up to set email alerts
|

The failure of transparency as self-regulation

Abstract: Purpose This paper aims to examine the existence of a transparency gap between voluntary external sustainability reporting and internal sustainability performance of an organisation arising from the operationalisation of transparency as an instrumental tool. Design/methodology/approach This study combined an analysis of a firm’s sustainability report (secondary data) with a qualitative case study data (primary data comprising interviews, meetings and internal documents) to understand how the Global Reporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…These examples may also suggest a key role of GRI in “setting standards in the public interest”. Leeson and Kuszewski (2023) support the discussion by Vigneau and Adams (2023) regarding the need to push stakeholder engagement to progress the quality of sustainability reporting. The difference is that while Vigneau and Adams (2023) refer to stakeholder engagement at the organisational level (e.g.…”
Section: New Insights Emerging In This Special Issue: Academic and Pr...mentioning
confidence: 85%
See 2 more Smart Citations
“…These examples may also suggest a key role of GRI in “setting standards in the public interest”. Leeson and Kuszewski (2023) support the discussion by Vigneau and Adams (2023) regarding the need to push stakeholder engagement to progress the quality of sustainability reporting. The difference is that while Vigneau and Adams (2023) refer to stakeholder engagement at the organisational level (e.g.…”
Section: New Insights Emerging In This Special Issue: Academic and Pr...mentioning
confidence: 85%
“…Leeson and Kuszewski (2023) support the discussion by Vigneau and Adams (2023) regarding the need to push stakeholder engagement to progress the quality of sustainability reporting. The difference is that while Vigneau and Adams (2023) refer to stakeholder engagement at the organisational level (e.g. taking stakeholders into account in the design of the materiality matrix and putting the results of this exercise into practice), as discussed above.…”
Section: New Insights Emerging In This Special Issue: Academic and Pr...mentioning
confidence: 85%
See 1 more Smart Citation
“…Voluntary disclosures following the GRI framework may also shape an external expression of acceptable corporate behaviour (transparency norm) that is different from the actual behaviour or performance of the company (Vigneau and Adams, 2023). Studies have revealed a transparency gap between voluntary external sustainability reporting using the GRI framework and internal sustainability performance (Zharfpeykan and Akroyd, 2022; Vigneau and Adams, 2023). Specifically, companies may not integrate GRI issues that they consider to be material in their internal performance measurement systems and report them externally (also supported by our study) (Zharfpeykan and Akroyd, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, companies may not integrate GRI issues that they consider to be material in their internal performance measurement systems and report them externally (also supported by our study) (Zharfpeykan and Akroyd, 2022). Therefore, the selective nature of voluntary reporting plus the disengagement of these reports from real sustainable activities highlights the importance of imposing mandatory sustainability reporting requirements to enhance accountability for all stakeholders (Vigneau and Adams, 2023).…”
Section: Discussionmentioning
confidence: 99%